Predictive ecology : a two-chapter analysis of lizard invasion and serpent potential invasion using ecological niche models in Brazil - Guimarães, Victor Hugo Silva (2024)
Tese (doutorado)—Universidade de Brasília, Programa de Pós-Graduação em Zoologia, 2024.